ANALYSIS OF PATIENT SATISFACTION LEVELS WITH INPATIENT INSTALLATION SERVICES AT SOEDARSONO DARMOSOEWITO HOSPITAL, BATAM CITY (PERIOD JULY – OCTOBER 2024) - Palapessy, Victor E.D; Susanti, Rini (PT Altin Riset Publishing, 2025)
This study aims to analyze patient satisfaction levels with inpatient services at Soedarsono Darmosoewito Hospital in Batam City from July to October 2024. The method used is a survey with a descriptive approach to describe the phenomenon of patient satisfaction. The sample of this study consists of 50 patients who were hospitalized, with the sampling technique of accidental sampling. Data collection was conducted through observation and interviews, as well as questionnaires measuring five service dimensions: tangible, reliability, responsiveness, assurance, and empathy. The results show that overall, patient satisfaction with inpatient services at Soedarsono Darmosoewito Hospital is positive. The dimensions of physical evidence, reliability, and empathy received good scores, with particular attention to cleanliness, comfort, and staff attitudes. However, several aspects need improvement, especially in communication and waiting times. This study provides recommendations for service improvements to enhance patient satisfaction.